A Conceptual Outlook Concerning Brand Management - SONI, VIBHA; AGRAWAL, DR. VINITA (The journal of contemporary issues in business and government, 2021)
According to the American market association (2010), brand is a term, symbol, name, design, term or any other attribute that can be used to identify the products or services of the company. Globalization has increased the competition in market, education has increased the level of customer awareness about the products, increased level of income has made people brand users and social aspect has made people using branded goods a symbol of social image. Thus, it is very important to understand for a marketer that having a brand is not enough but the effective brand management is also important. Everyday new products, substitutes are coming in the market with innovative features, and attractive prices. In this situation, it is one of difficult issue or challenge to deal with brand management. It is important question before the managers to know that how to maintain the brand equity in the continuously changing environment, where the needs and expectations of the customers are changing continuously. The three important elements of brand equity are brand awareness, brand association and brand loyalty. Brand awareness shows the level of customers to identify the product of the company, brand associations shows the associations between brand and the customer and brand loyalty shows the loyalty of the customers towards the brand. These three elements of the brand equity help in managing a brand by the company.